The Effect of Cash Turnover and Operating Income on Net Profit at PT Bumi Resources Tbk - Restian Dwi Wijaya (CV. Era Digital Nusantara, 2026)
This study analyzes the partial and simultaneous effects of cash turnover and operating income on net profit at PT Bumi Resources Tbk from 2013 to 2023. Employing a quantitative associative design, this research utilizes audited financial statement data from the Indonesia Stock Exchange, processed via multiple linear regression analysis. The novelty lies in examining the sensitivity of a systemic mining giant's profitability amid post-pandemic global commodity price volatility and regulatory shifts. The results reveal that cash turnover has a negative and significant effect on net profit, indicating transactional inefficiencies during rapid cash cycles. Conversely, operating income has a negative but non-significant effect, proving that top-line growth fails to secure profitability when eroded by soaring operational cost overruns. Simultaneously, both variables exert a positive and significant impact, explaining 66.8% of the net profit variance. This underscores the critical need for integrated capital governance to navigate market shocks.